GALSAN TSCHINAG’IN KERVAN ADLI ROMANINDA HATIRLAMA FİGÜRLERİNİN İZDÜŞÜMLERİ - Baytimur, Nazlı Memiş (Fırat University, 2021)
Galsan Tschinag, edebiyat ve kültür sahasında kendini geliştirmiş bir grup olan Tsengel Tuvalarına mensup bir yazardır. Sayısı otuz beşi aşan şiir, öykü, roman, hatıra vb. edebi türlerde Almanca basılan kitapları birçok farklı dile çevrilmiştir. Yazarın söz konusu eserlerinden birisi de Almanca Die Karawane olarak yayımlanan ve Prof. Dr. Nurettin Demir tarafından günümüz Türkçesine aktarılan Kervan adlı romandır. Tschinag, romanı aracılığıyla özünden uzaklaşıp ona yabancılaşmaya başlayan Tuva toplumunun bugününe, Tuvaların meydana getirdiği imgeler ve geçmişten taşınan hatırlama figürleri ile olumlu yönde etki etmeye çalışır. Kavramlar, semboller ve deneyimler gibi toplumun düşünceler sistemini oluşturan unsurlar arasındaki ilişki, hatırlama figürlerini ortaya çıkarır. Söz konusu figürler, zamana ve mekâna bağlılık, gruba bağlılık ve tarihin yeniden kurulması özellikleri ile ayırıcı bir nitelik kazanır. Tuvaların kültürel ürünleri ile taşınan çok boyutlu izler, yazarın kurguda hatırlama figürlerinden yararlanması sonucunda geçmişten gelerek günü anlamlandırır. Bu çalışma, Kervan adlı romanın kurgusunda hatırlama figürlerinin kullanım şekillerini göstermeyi hedeflemektedir.

Galsan Tschinag is a writer belonging to Tsengel Tuvas, a group that has developed itself in the field of literature and culture. More than thirty five poems, short stories, novel, memoirs and similar literary genres, published in German, have been translated into many languages. One of the author’s works in question was published as Die Karawane in German and was translated into modern Turkish by Prof. Dr. Nurettin Demir. This novel was called as Kervan in Turkish. Through his novel, Tschinag tries to positively influence the present of the Tuva society, which has started to alienate itself from its essence, with the images created by the Tuvas and the remembering figures carried from the past. The relationship between the elements that make up the society’s system of thoughts, such as concepts, symbols and experiences reveals figures of remembering. The figures in question acquire a distinctive character with their loyalty to time and space, loyalty to the group and reconstruction of history. The multidimensional traces carried by the cultural products of Tuvas make sense of the day coming from the past as a result of the author’s use of recall figures in fiction. This study aims to show the usage of remembering figures in the fiction of the novel called Kervan.
The Projections of the Figures of Remembering in Galsan Tschinag’s Novel Called Caravan